Via walled cavities as vertical transitions in multilayer microwave and millimeterwave circuits - Swierczynski, Tom (University of Ottawa (Canada), 2004)
This thesis describes the development and realization of a novel method of transferring energy vertically through any number of substrate layers of a printed circuit board at microwave and millimeter wave frequencies. The motivation for this thesis has been the need for a high performance, small size and low cost vertical interconnect circuit which can be used in wireless applications. In particular, array antenna applications often require vertical interconnects in beam forming networks or to couple signals from the beam forming network to the radiating elements. Therefore, the transfer of energy vertically through several layers of printed circuit board is an essential means to pass information for further processing. This thesis initially discusses and evaluates recent developments produced within the microwave industry on this topic through a concise review of the literature. Shortcomings of current techniques to transfer energy vertically at microwave and millimeter wave frequency are identified and discussed. The main objective of this thesis was to determine vertical interconnect solutions to operate at any microwave and millimeter wave frequencies, that can be easily implemented using current printed circuit board (PCB) technology and to provide flexibility to construct multiple substrate layer transitions between two microstrip lines by the use of via walled cavities. This was done through the undertaking of both the simulations and practical realization of a vertical interconnect design. With this objective, the techniques and methodology as well as design guidelines are developed and discussed. Various cavity types and circuit configurations are presented with tradeoff analyses. Also, a manufacturing tolerance study is presented to show that this novel method of transferring energy can be used in applications at microwave and millimeter wave frequencies.
Keywords: Engineering, Electronics and Electrical.; Engineering, Materials Science.